2018
DOI: 10.1002/spp2.1234
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Ediacaran rangeomorph Charnia masoni

Abstract: The Ediacaran macrofossil Charnia masoni Ford is perhaps the most iconic member of the Rangeomorpha: a group of seemingly sessile, frondose organisms that dominates late Ediacaran benthic, deep‐marine fossil assemblages. Despite C. masoni exhibiting broad palaeogeographical and stratigraphical ranges, there have been few morphological studies that consider the variation observed among populations of specimens derived from multiple global localities. We present an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 69 publications
4
30
0
Order By: Relevance
“…Of these groups, rangeomorphs are not only the most diverse but display the greatest anatomical variation (Shen et al, 2008;Xiao and Laflamme 2009). Some rangeomorphs are preserved as single fronds (e.g., Charnia), but others were bushy (e.g., Bradgatia), spindle-shaped (e.g., Fractofusus) or arborescent (e.g., Primocandelabrum) (Gehling and Narbonne 2007;Bamforth et al, 2008;Flude and Narbonne 2008;Bamforth and Narbonne 2009;Dunn et al, 2019). Rangeomorph branches differentiated directly from one another or from a central stalk (Dunn et al, 2019) and some rangeomorphs additionally exhibited a naked stem that elevated the frond into the water column (Laflamme et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of these groups, rangeomorphs are not only the most diverse but display the greatest anatomical variation (Shen et al, 2008;Xiao and Laflamme 2009). Some rangeomorphs are preserved as single fronds (e.g., Charnia), but others were bushy (e.g., Bradgatia), spindle-shaped (e.g., Fractofusus) or arborescent (e.g., Primocandelabrum) (Gehling and Narbonne 2007;Bamforth et al, 2008;Flude and Narbonne 2008;Bamforth and Narbonne 2009;Dunn et al, 2019). Rangeomorph branches differentiated directly from one another or from a central stalk (Dunn et al, 2019) and some rangeomorphs additionally exhibited a naked stem that elevated the frond into the water column (Laflamme et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[10,[44][45][46][47][48]; a pattern that is consonant across the small skeletal, carbonaceous and trace fossil records [47]). To wit: at around 571 Ma or so appear fossils that may be assigned to stem or early crown group animals [36,37,[49][50][51]; at around 566 Ma comes the first evidence of eumetazoan-grade organisms in the form of trace fossils [52]; no later than around 555 Ma are found complex (i.e. bilaterian) trace fossils and taxa assignable to stem cnidarian, ctenophore and bilaterian grades [14,36]; by around 545 Ma near the end of the Ediacaran comes a diversification of large trace fossils (assignable to late stem and perhaps early crown group bilaterians [53]); and rather early in the Cambrian, perhaps 535 Ma come the first definitive crown group bilaterians (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1D), implying that, at some point following death, the branches must have been "inflated" and presumably interconnected to allow sediment to circulate without baffling. A boundary appears to have existed between second-order branches at the time of infill [e.g., Dunn et al (11), figure 10C], demonstrated by the ease with which individual second-order branches can be separated into discrete units with smooth faces. Tomographic data confirm these patterns (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The function of the interconnected compartments is unclear, but Butterfield (10) advanced a hypothesis that each individual secondorder branch had its own gastrovascular cavity, with higher-order branches functioning as mesenteries. However, previous work has shown the independent mechanical flexibility of such structures [e.g., (11)], which is incompatible with a mesentery-like function. Furthermore, our XTM data show no evidence for internal strut-like projections, despite sufficient resolution in fossil preservation and x-ray tomography (Fig.…”
Section: Anatomical Organization Of Charnia and Rangeomorphamentioning
confidence: 99%